2014
DOI: 10.2355/isijinternational.54.2713
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation Behavior of Quasi-particle Comprising High Alumina Pisolitic Ore

Abstract: This study aims to utilize the high Al2O3 pisolitic ore in sintering process by designing the quasi-particle where the pisolitic ore is used as nuclei and ultra-fine hematite and magnetite ores are employed as adhering fines. The assimilation behavior between nuclei and adhering fines was investigated through microstructure analysis and it was correlated to sinter quality. When ultra-fine hematite ore was used as adhering fines, the low viscous melt of CaO·Fe2O3 was formed in the assimilation. Since this resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As shown in Table 3, the use of ultrafine magnetite ore (PF-J) as adhering fines showed approximately 55°C higher maximum temperature of exhausted gas compared with that of ultrafine haematite ore (PF-N) due to the oxidation of magnetite ores during sintering. Recently, Jeon et al 12 reported that the formation of a high viscosity interfacial layer on the boundary between high Al 2 O 3 iron ores used as nuclei and ultrafine magnetite iron ores used as the adhering fines effectively localised Al 2 O 3 in the centre of granules, which lead to the improvement of sinter strength.…”
Section: Results Of Sinter Pot Testmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 3, the use of ultrafine magnetite ore (PF-J) as adhering fines showed approximately 55°C higher maximum temperature of exhausted gas compared with that of ultrafine haematite ore (PF-N) due to the oxidation of magnetite ores during sintering. Recently, Jeon et al 12 reported that the formation of a high viscosity interfacial layer on the boundary between high Al 2 O 3 iron ores used as nuclei and ultrafine magnetite iron ores used as the adhering fines effectively localised Al 2 O 3 in the centre of granules, which lead to the improvement of sinter strength.…”
Section: Results Of Sinter Pot Testmentioning
confidence: 99%
“…From a microscopic viewpoint, the gangue components such as Al and Si contained in high Al 2 O 3 iron ores could be localised by coating the surface of high Al 2 O 3 iron ores (G) with ultrafine iron ores containing low Al 2 O 3 , which limits the dissolution and diffusion of the gangue components into primary sinter melts, leading to the minimisation of the adverse impact on sinter quality. 12 The selective granulation of high Al 2 O 3 iron ores and ultrafine iron ores would increase the relative amount of flux (limestone) and fuels in sinter blends, which consequently leads to the promotion of primary melt formation. 18 As a result, the proper selective granulation of high Al 2 O 3 ores and ultrafine iron ores would make great contribution to the improvement of sintering productivity as well as sinter quality such as strength and RDI.…”
Section: Effect Of Mini-pellets By Selective Granulation On Sintering...mentioning
confidence: 99%
See 1 more Smart Citation
“…Jeon et al, studied the assimilation behavior of quasi-particle-comprised, high alumina pisolitic ore. The results showed that the quasi-particle comprised high Al 2 O 3 pisolitic ore and ultra-fine magnetite ore obtained high sinter quality [17]. Umadevi et al, revealed that with increasing alumina content in the sinter of both the conventional and selective granulation processes, the fractions of hematite and of SFCA, and the pore phase increased, whereas the magnetite and silicate phases decreased [18].…”
Section: Introductionmentioning
confidence: 99%
“…There is a history of efforts to understand the roles of ore fines and coarse particles in assimilation and matrix formation in the scientific literature [20][21][22][23][24]. However, most of it is based on experiments conducted in laboratory-scale electric furnaces.…”
Section: Introductionmentioning
confidence: 99%